Aplikasi Web Pengingat Registrasi Mahasiswa Berbasis SMS (Short Message Service) Gateway Studi Kasus : Universitas Tribuana Kalabahi - Lasarus Pelipus Malese; Jon Idrison Molina (Jurnal Ilmiah Wahana Pendidikan, 2021)
The student registration system at Tribuana Kalabahi University (UNTRIB), is held only within the period according to the academic calendar of the semester. The registration stage is carried out 2 (two) times each semester, namely registration for the cost of Educational Development Contributions (SPP) and registration for Semester Credit Unit (SKS) fees. Registration payments made by students are often not on time according to the academic calendar. This has a negative impact on the sustainability of student learning itself because the rights to academic services are limited, including the right to lectures, practicums, field work practices, field introduction practices, academic guidance/advising, thesis writing guidance, and even thesis examinations. Another consequence is that there are arrears in payments in each semester with different batches in 10 (ten) study programs reaching r± Rp. 2.264.690.000,- (two billion two hundred sixty four million six hundred ninety thousand rupiah). This can be overcome by designing a web application based on SMS (Short Message Service) gateway that can send administrative registration schedule messages to all students, this designed system can also send registration delay messages (fines) on student cellphones who fail to register, Research methods used is an iterative method. In general, in software development in the iterative model, there are stages which include: requirements, analysis, system design, implementation, and review. Analysis of the requirements for system design and implementation is carried out through the stages of making a UML (Unified Modeling Language) Model. Meanwhile, the analysis of software requirements uses the Apache Web server, server-side scripting PHP, Gammu as an SMS gateway application and a web-based MySQL database that is bundled in Apache. The application that was built has succeeded in sending an administrative registration schedule message to all Tribuana Kalabahi University students in different semesters and batches as well as a delay message (fine) for students who fail to register administratively.